Technology engineering and management in aviation advancements and discoveries - Abu-Taieh, Evon M.O; Jafari, Mostafa; El-Sheikh, Asim A. (Information Science Reference, 2012)
This book details the essential new developments in technology and management in the aviation industry, specifically important advances in navigation, air traffic control, and environmental impact